Images of Lake Lucerne. - Fischer, Peter; Fluor-Bürgi, Regine; Lichtin, Christoph; Papiro, Martina (Luzern : Kunstmuseum Luzern, 2006)
Calamé, Alexandre ; Corinth, Lovis ; Donatello & Fosco Dubini ; Dubach, Margaretha ; Emmenegger, Hans ; Hostettler, Heidi ; Krystufek, Elke ; Nordman, Maria ; Odermatt, Arnold ; Pfeiffer, Otto ; Regli, Peter ; Richter, Gerhard ; Rütimann, Christoph ; Turner, William ; Wick, Cecile ; Zürcher, Renatus
Engels
Exhibition. Images of Lake Lucerne. Kunstmuseum Luzern, 10.06.2006 - 01.10.2006.
boek
Keywords: Luzern